The Influence of Social Media Promotion and Direct Selling on the Decision to Buy Tickets for the 2024 Medan Relaxing Purnama Concert - Jati, Giri Waseso; Siregar, Efni (CV. Civiliza Publishing, 2025)
This research aims to determine the influence of social media promotion and direct selling on ticket purchase decisions for the Purnama Bersantai 2024 concert in Medan City. The study is motivated by the growing use of social media as a promotional tool and the implementation of direct selling strategies to attract consumer interest. This study employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 98 respondents who purchased concert tickets. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The results show that social media promotion has a positive and significant effect on purchase decisions, as does direct selling. Simultaneously, both variables significantly influence ticket purchase decisions for the Purnama Bersantai 2024 concert. The coefficient of determination (R²) of 0.694 indicates that 69.4% of purchase decisions are influenced by social media promotion and direct selling, while the remaining 30.6% are influenced by other factors. The study concludes that the more effective social media promotion and direct selling activities are, the higher the consumers’ decision to purchase concert tickets.